The Demersal Fish Community on the West Spitsbergen Shelf. Biodiversity, species composition, distribution and temporal changes in relation to climate. - Born, Mathea (UiT Norges arktiske universitet, 2020)
This thesis explores a historical time series of trawl stations on the West Spitsbergen Shelf (WSS), aiming to understand the spatial and temporal variability of the demersal fish communities in the region. Abundance data of 42 fish species are used to investigate the species composition, richness, and diversity across six different areas under different environmetal influence. The results indicate a separation in the fish community between Arctic and Atlantic on the WSS. This Arctic-Atlantic separation is most evident in the first decade of the survey but seems to be weakening towards the end of the studied period. Additionally, the fish species composition on the shelf appears to be affected by the decadal variability of the NAC, converging towards a more similar composition during warm periods and diverging during colder periods. Although species richness and diversity show sharp interannual fluctuations throughout the time series, an increase in diversity was detected in one of the Arctic areas. In contrast, its Atlantic counterpart showed the opposite trend. These results might indicate that the fishes on the continental slope are moving further in on the shelf, adding richness and diversity to these areas while changing the species composition towards a more Atlantic community.